SmallSats: a new technological frontier in ecology and conservation?. Issue 2 (1st October 2021) - Curnick, David J.; Davies, Alasdair J.; Duncan, Clare; Freeman, Robin; Jacoby, David M. P.; Shelley, Hugo T. E.; Rossi, Cristian; Wearn, Oliver R.; Williamson, Michael J.; Pettorelli, Nathalie
Abstract: We are in the midst of a revolution in satellite technology, with the rapid development and advancement of small satellites (or SmallSats, i.e., satellites <180 kg). Here, we review the opportunities and challenges that such technology might afford in the field of conservation and ecology. SmallSat constellations may yield higher resolutions than those that are currently available to scientists and practitioners, increasing opportunities to improve environmental‐monitoring and animal‐tracking capabilities. They may cut access costs to end users, by reducing operational costs and bringing increased competition to the existing market. Their greater flexibility and affordability may moreover enable the development of bespoke constellations for specific conservation and ecological applications, and provide greater interoperability with ground‐based sensors, such as tracking devices and camera traps. In addition, SmallSats may serve as cost‐effective research and development platforms for new components and products. Combined, these benefits could significantly improve our ability to monitor threats to the environment as they unfold, while enhancing our understanding of animal ecology and ecosystem dynamics. However, significant hardware and software developments are required before such technology is able to produce, process and handle reliable and cost‐effective data, and the initial research and development costs still represent a major challenge. Further, we argue that much remains to be done to ensure these new data products become accessible, equitable and sustainable. Abstract : SmallSats have the potential to revolutionise remote sensing. At this important stage in their development and deployment, we review the opportunities that this technology might afford in the field of conservation and ecology. Furthermore, we highlight the possible challenges that lie ahead and consider the technological, ethical and policy considerations to ensure that they become a valuable addition to the research toolbox.